Hypertension burden and control in mainland China: Analysis of nationwide data 2003–2012. (1st April 2015) - Li, Dianjiang; Lv, Jun; Liu, Fangchao; Liu, Pei; Yang, Xueli; Feng, Yating; Chen, Gang; Hao, Mo
Abstract: Background: No nationwide survey on hypertension was conducted in China since 2002. We assessed the prevalence, awareness, treatment, and control of hypertension in mainland China and in various regions using nationwide data from 2003 to 2012. Methods and results: We identified studies that reported age- and gender-specific prevalence and/or age-specific awareness, treatment and control of hypertension in representative population samples from 31 provinces, using China National Knowledge Infrastructure, Wanfang and PubMed, supplemented by a manual search of references of retrieved articles. All data were extracted independently by two investigators using a standardized data-collection form. Overall, 265 million adults (145 million men and 120 million women) had hypertension for a prevalence of 26.7% (28.9% among men and 24.5% among women) in 2010. Among hypertensive patients, only 44.6% were aware of their condition, 35.2% were taking antihypertensive medication, and 11.2% achieved adequate blood pressure control. There were substantial geographic variations in the prevalence and control of hypertension. Hypertension prevalence was the highest in east region (32.6%) followed by northeast region (31.8%). Worse still, the control rate among hypertensive people was very poor in southwest (4.8%) and northeast (5.9%) regions. Conclusions: Hypertension is highly prevalent in mainland China, with inadequate awareness, treatment, and control of hypertension. Effective strategies are urgently needed in China, especially in the regions with high prevalence and low control. Highlights: The prevalence of hypertension varied geographically within China. There was adverse trend in hypertension prevalence in the next 20 years. Awareness, treatment, and control of hypertension remained at unacceptably low levels.